Spatial Partitioning of Microbial Functional Potential Suggests Complex Nitrogen Cycling in a Subterranean Estuary - Daniel Romano‐Gude; Nestor Arandia‐Gorostidi; Catalina Mena; Marc Diego‐Feliu; Bella Almillategui; Anna J. Székely; Stefan Bertilsson; Andrea G. Bravo; Jesus Carrera; Cristina Romera‐Castillo; Albert Folch; Jordi Garcia‐Orellana; et al. (Environmental Microbiology, 2026)
Subterranean estuaries (STEs) are key bioreactors regulating the quantity and chemical composition of groundwater‐derived nitrogen (N) reaching coastal ecosystems. Yet, the microbial controls on N‐cycling within these groundwater–seawater mixing zones remain poorly understood. We investigated the spatio‐temporal variations in microbial communities and their N‐cycling potential within an alluvial Mediterranean STE with high N concentration. We explored changes in microbial abundance, heterotrophic activity, taxonomic composition, and the abundance of N‐cycling genes across groundwater samples collected at several depths and distances from the shoreline in winter and summer. Microbial abundance, activity, and diversity varied strongly across hydrochemical zones according to physicochemistry and aquifer depth but showed limited seasonality. Functional predictions suggested a complex, spatially structured suite of N pathways encoded by diverse taxa occupying different STE zones, and quantitative‐PCR revealed niche partitioning between ammonia‐oxidizing archaea, prevalent in fresh‐groundwater, and bacterial denitrifiers enriched in deep‐saline layers. Multiple linear model predictions showed a stronger fit for NO 2 − and NH 4 + concentrations when using microbial properties than when using environmental variables, highlighting their importance for understanding N cycling in STEs. Our results suggest that the functional potential of the STE microbiome is complex and spatially structured across hydrochemical zones, explaining spatial variations in STE N‐cycling.